2006
DOI: 10.1111/j.1460-9592.2006.01957.x
|View full text |Cite
|
Sign up to set email alerts
|

Intraoperative and postoperative risk factors for prolonged mechanical ventilation after pediatric cardiac surgery

Abstract: Causes of MV after surgery are heterogeneous, vary with time, and have variable impact on the duration of MV.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
113
0
11

Year Published

2009
2009
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 108 publications
(127 citation statements)
references
References 25 publications
3
113
0
11
Order By: Relevance
“…1,3,14) A long CPB time was consistently associated with prolonged mechanical ventilation and serious bleeding after open-heart surgery. In addition, this was associated with an increased risk of inflammatory response syndrome and cardiac edema, resulting in delayed sternal closure, decreased respiratory compliance, acute lung injury, and coagulopathy or serious bleeding.…”
Section: Extubation In or After Congenital Heart Surgerymentioning
confidence: 99%
“…1,3,14) A long CPB time was consistently associated with prolonged mechanical ventilation and serious bleeding after open-heart surgery. In addition, this was associated with an increased risk of inflammatory response syndrome and cardiac edema, resulting in delayed sternal closure, decreased respiratory compliance, acute lung injury, and coagulopathy or serious bleeding.…”
Section: Extubation In or After Congenital Heart Surgerymentioning
confidence: 99%
“…The analysis of the progression of the children with and without respiratory complications showed that these postoperative complications determine a longer mechanical ventilation time and hospitalization, factors that are known to affect surgical success. However, after seven days on mechanical ventilation, it is difficult to differentiate complications that are secondary to heart disease from those caused by the need to receive prolonged ventilation support (16) , such as pneumonia. The different diagnoses and surgical techniques used, as well as the therapies chosen for the postoperative care, make this analysis difficult, and it is not possible to assign a causal relation to respiratory complications.…”
Section: Discussionmentioning
confidence: 99%
“…In international studies, Székely et al (16) evaluated a group of 411 children that underwent heart surgery and found a mortality rate of 3.2%. However, those authors stress that 15 of those children were transferred to other medical services and two died after hospital discharge.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have reported mixed findings regarding the association of higher fluid intake volumes and longer duration of mechanical ventilation Szekely et al, 2006 .…”
Section: Fluid Intake Volume and Postoperative Outcomesmentioning
confidence: 99%
“…A limited number of studies have evaluated fluid intake in infants with congenital heart defects who are recovering from cardiac surgery Szekely, Sapi, Kiraly, Szatmari, & Dinya, 2006). identified fluid restriction as the major barrier to providing adequate nutrition, with fluid restriction defined as less than 80% of daily maintenance fluid requirements.…”
Section: Postoperative Fluid Volumes In Clinical Practicementioning
confidence: 99%